CURRICULUM COMPARISON OF ENGINEERING FACULTY, TECHNOLOGY FACULTY AND TECHNICAL EDUCATION FACULTY: CASE STUDY OF MECHANICAL AND ELECTRICAL ENGINEERING - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2014)
Curriculums are prepared for a specific purpose. The related purpose determines the role of institution, namely, the purpose defines the responsibility and functions of the school. The purposes guide for selection of experienced academic staff, and development of student characteristics. The purpose of engineering education is to bring up individuals who might contribute to scientific and educational development in the country. To accomplish this purpose, engineering curriculum should found on strong mathematics, applied and human sciences and there should be relation between applications and theory. On the other hand, the purpose of technical teacher's education is to educate the individuals who could work as either technical teacher or technical personnel when needed. Those should have pedagogical formation besides the characteristics mentioned before. In this respect, a technical teacher who is both technical teacher and technical personnel is required to have a preparation education relying on three dimensions such as liberal education, pedagogical formation and special education. These dimensions of profession of a teacher could be implemented both in a single institution within a single program and also, in various institution within various programs. In this study, curriculum of higher educational institutions that have taken to educate either engineer or technical teacher on task, has been come up, compared each other and how strong relation there is between theory and application is revealed.
Keywords: Curriculum comparison; Technology Faculty; Technical Education Faculty; Engineering Faculty